The Influence of Brand Communication on Brand Equity via Instagram (Case Study of Bright Gas Products) - Wicaksono, Hanggowo; Hadiprawoto, Triana Rahajeng (International Journal of Business Studies, 2024)
This research aims to analyze the influence brand communication towards brand equity via Instagram user Bright Gas. This research also investigates the role of instagram marketing activites to brand awareness, brand image and perceived quality and its relationships to positive word of mouth and brand instagram re-usage intention, This research is a quantitative research that uses an online questionnaire and obtained a total sample of 301 respondents who were processed using the SmartPLS version 3 application. The partial research results show that instagram marketing activities has significant positive effect on brand awareness, brand image and perceived quality, while brand awareness, brand image and perceived quality partially has a positive and significant effect on positive word of mouth and brand instagram re-usage intention, This research succeeded in finding a form attitudinal loyalty with variable operation positive e-wom and behavioral loyalty on variables brand instagram re-usage intention which specifically researches online platform users.